Nannochloropsis as an Emerging Algal Chassis for Light-Driven Synthesis of Lipids and High-Value Products - Ying Ye; Meijing Liu; Lihua Yu; Han Sun; Jin Liu (Marine Drugs, 2024)
In light of the escalating global energy crisis, microalgae have emerged as highly promising producers of biofuel and high-value products. Among these microalgae, Nannochloropsis has received significant attention due to its capacity to generate not only triacylglycerol (TAG) but also eicosapentaenoic acid (EPA) and valuable carotenoids. Recent advancements in genetic tools and the field of synthetic biology have revolutionized Nannochloropsis into a powerful biofactory. This comprehensive review provides an initial overview of the current state of cultivation and utilization of the Nannochloropsis genus. Subsequently, our review examines the metabolic pathways governing lipids and carotenoids, emphasizing strategies to enhance oil production and optimize carbon flux redirection toward target products. Additionally, we summarize the utilization of advanced genetic manipulation techniques in Nannochloropsis. Together, the insights presented in this review highlight the immense potential of Nannochloropsis as a valuable model for biofuels and synthetic biology. By effectively integrating genetic tools and metabolic engineering, the realization of this potential becomes increasingly feasible.